THE EFFECT OF NIHSS CLINICAL SCORE OUTPUT TOWARD DELIRIUM INCIDENT ON STROKE PATIENT - Diah Retno Wulan; Bella Aldila Erlida (Journal of Nursing Invention, 2020)
The incidence of stroke is quite high each year and the problem can have to more serious problem if it is handled slowly. The severity of stroke patients needs to be measured to help doctors and nurses determine the right treatment and National Institute of Health Stroke Scale (NIHSS) is the valid instrument that can be used . One of the neurological disorders that can be experienced by stroke patients associated with stroke severity is delirium. Early detection of delirium is very important to allow immediate treatment that can help reduce bad prognosis. The objective of this study is to know the effect of NIHSS clinical score output toward delirium incident on stroke patients. The research method used analytical research design with cross sectional approach, the sample was stroke patients who were treated at the Stroke Center Room in Ulin Hospital Banjarmasin, a total of 52 people. The sample is taken by probability sampling method. Data were analyzed using Wilcoxon test. By this study it were found that the stroke severity of patients was mild (5.8%), moderate (38.5%), severe (23.1%), and very severe (32.7%). Patients who experienced delirium were 61.5% and did not experience 38.5%. Based on statistical test, it was stated that the p value was 0.001, which described the significant effect of NIHSS clinical value output on the occurrence of delirium on stroke patients. A significant effect is that the higher the clinical value output of NIHSS, the greater the delirium incident on stroke patients. Angka kejadian stroke cukup besar setiap tahunnya dan masalah tersebut dapat berdampak pada masalah yang lebih serius jika tidak ditangani dengan segera. Tingkat keparahan pada pasien stroke perlu diukur untuk membantu dokter maupun perawat menentukan perawatan yang tepat dan salah satu instrumen penilaian yang dianggap valid untuk menilainya adalah National Institute of Health Stroke Scale (NIHSS). Salah satu gangguan neurologis yang dapat dialami oleh pasien stroke terkait dengan tingkat keparahan stroke adalah keadaan delirium. Deteksi dini delirium sangat penting untuk memungkinkan perawatan segera yang dapat membantu mengurangi kemungkinan prognosis buruk. Penelitian ini bertujuan untuk mengetahui pengaruh output nilai klinis NIHSS terhadap kejadian delirium pada pasien stroke. Desain penelitian yang digunakan dalam penelitian ini adalah cross sectional, sampel adalah pasien stroke yang dirawat di Ruang Stroke Center RSUD Ulin Banjarmasin sebanyak 52 orang, yang diambil dengan metode probability sampling. Data dianalisis menggunakan uji Wilcoxon. Hasil penelitian didapatkan tingkat keparahan stroke pasien adalah ringan (5,8%), sedang (38,5%), berat (23,1%), dan sangat berat (32,7%). Pasien yang mengalami delirium sebanyak 61,5% dan tidak mengalami sebanyak 38,5%. Berdasarkan uji statistik dinyatakan nilai p value sebesar 0,001 yang menggabarkan adanya pengaruh bermakna output nilai klinis NIHSS terhadap kejadian delirium pada pasien stroke. Adanya pengaruh yang bermakna yaitu semakin tinggi output nilai klinis NIHSS maka semakin besar kemungkinan terjadinya delirium pada pasien stroke.